Tailoring the Structure, Energy Storage, Strain, and Dielectric Properties of Bi0.5(Na0.82K0.18)0.5TiO3 Ceramics by (Fe1/4Sc1/4Nb1/2)4+ Multiple Complex Ions - Huo, Ziwei; Xie, Hang; Xu, Jiwen; Yang, Ling; Qiu, Wei; Zhang, Xiaowen; Zhou, Changrong; Wang, Hua (Frontiers in Materials, 2020)
The effects of (Fe1/4Sc1/4Nb1/2)4+ (FSN) multiple complex ions on the structure and electrical properties of Bi0.5(Na0.82K0.18)0.5Ti(1-x)(Fe1/4Sc1/4Nb1/2)xO3 (BNKT-xFSN) ceramics were studied. The FSN complex ions induces the phase transition from ferroelectric state to relaxor state. The coercive field and remanent polarization decrease rapidly with the increase of FSN content. With the increase of the external electric field, the energy storage density of BNKT-xFSN ceramics gradually increases and reaches the maximum value of 0.96 J/cm3 (90 kV/cm) at x=0.09, and the corresponding efficiency is 62%. Meanwhile, the field-induced strain of BNKT-0.07FSN ceramic increases from 0.13% at 50 kV/cm to 0.43% at 80 kV/cm, and the corresponding electrostrictive coefficient Q33 reaches the maximum value of 0.0213 m4/C2. BNKT-xFSN relaxed ceramics with pseudo-cubic structure have large electrostrictive coefficients when TF-R is near room temperature. The local composition inhomogeneity by FSN complex ions at B-sites induces the relaxor characteristics of BNKT-xFSN ceramics.